Chapter Al di là del rapporto di lavoro: fenomenologie e stili del potere datoriale - CORAZZA, Luisa (Studi e saggi, 2022)
The essay aims at investigating new forms and styles of the power of the employer. Since the main regulatory intervention on employment relationship (above all the Statuto dei lavoratori ) significant changes occured in the context were the relationship performs, so that a rethinking of the basis of employer's power is required. The role of labour market, new forms of organization of the firm and the diversification of workers types are few of different examples of this changing context. Therefore, regulatory tecniques need a refoundation, taking into account that the power of the employer performs not only within the employment relationship but also outside the employment relationship.